Performance of Wells Score for Deep Vein Thrombosis in the Inpatient Setting - Silveira, Patricia C; Ip, Ivan K; Goldhaber, Samuel Z; Piazza, Gregory; Benson, Carol B; Khorasani, Ramin (JAMA internal medicine, 2015)
The Wells score to determine the pretest probability of deep vein thrombosis (DVT) was validated in outpatient settings, but it is unclear whether it applies to inpatients. To evaluate the utility of the Wells score for risk stratification of inpatients with suspected DVT. A prospective study was conducted in a 793-bed quaternary care, academic hospital using Wells score clinical predictor findings entered by health care professionals in a computerized physician order entry system at the time lower-extremity venous duplex ultrasound studies were ordered. All adult inpatients suspected of having lower-extremity DVT who underwent lower-extremity venous duplex ultrasound studies between November 1, 2012, and December 31, 2013, were included. Patients with DVT diagnosed within the prior 3 months were excluded. For patients undergoing multiple lower-extremity venous duplex ultrasound studies, only the first was included. Our primary outcome was the Wells score's utility for risk stratification among inpatients with suspected DVT as measured by the difference in incidence of proximal DVT among the 3 Wells score categories (low, moderate, and high pretest probability), the discrimination accuracy of the Wells score categories as the area under the receiver operating characteristics curve, the failure rate of Wells score prediction, and the efficiency of the Wells score to exclude DVT. In a study cohort of 1135 inpatients, 137 (12.1%) had proximal DVT. Proximal DVT incidence in low, moderate, and high pretest probability groups was 5.9% (8 of 135), 9.5% (48 of 506), and 16.4% (81 of 494), respectively (P < .001). The area under the receiver operating characteristics curve for the discriminatory accuracy of the Wells score for risk of proximal DVT identified on lower-extremity venous duplex ultrasound studies was 0.60. The failure rate of the Wells score to classify patients with a low pretest probability was 5.9% (95% CI, 3.0%-11.3%); the efficiency was 11.9% (95% CI, 10.1%-13.9%). The Wells score performed only slightly better than chance for discrimination of risk for DVT in hospitalized patients. It had a higher failure rate and a lower efficiency in the inpatient setting compared with that reported in the outpatient literature. Therefore, the Wells score risk stratification is not sufficient to rule out DVT or influence management decisions in the inpatient setting.